Determining the Impact of Probicon L28 and BioPlus 2B on Finishing Pig Growth Performance and Carcass Characteristics - Macie E. Reeb; Jimeng Bai; Mike D. Tokach; Jordan T. Gebhardt; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jessie L. Vipham; Qing Kang; John W. Schmidt; Dayna M. Brichta-Harhay; Morgan Miller; et al. (Kansas Agricultural Experiment Station Research Reports, 2023)
These data represent the growth performance of pigs enrolled in a study to determine the impact of two direct fed microbial products onSalmonellaandEscherichiacoli prevalence pre- and post-harvest. A total of 650 finishing pigs in two groups were randomly assigned to pen via a completely randomized design, and pens were assigned to one of three treatments: 1) a control treatment with pigs fed a standard corn-soybean meal finishing diet (with no added probiotic); 2) the control diets with Probicon L28 (NexGen Innovations, LLC, Lubbock, TX) supplemented through water lines using a water medicator system at a target concentration of 1.0 × 106 CFU/head/day; and 3) the control diet with added BioPlus 2B (5.0 × 108 CFU/lb of feed; 3.0 × 109 CFU/ head/day; CHR Hansen, Inc, Milwaukee, WI). No evidence of difference (P>0.10) between treatments was observed for overall ADG, ADFI, or F/G or any of the carcass traits. However, there was a tendency for a treatment effect for loin depth (P= 0.070). Pigs fed the BioPlus 2B treatment had numerically greater loin depth compared to other treatments, but there were no significant pairwise differences between treatments (P>0.05). The results of this study suggested that probiotics used in this study and supplied through the water or feed had no impact on growth or carcass characteristics of finishing pigs.
Keywords: Probiotics; Probicon L28; BioPlus 2B; market pigs; performance; pre-harvest interventions